Linux & OpenVMS interoperability : tricks for old dogs, new dogs, and hot dogs with open systems - Wisniewski, John Robert (Compact solutions., 2003)
Make OpenVMS High Availability systems and low cost Open System computers work together in complex Intranet and Internet environments. Users of Linux, UNIX and the hundreds of thousands of OpenVMS installations world-wide will find invaluable information in Linux and OpenVMS Interoperability. This book gives you access to the best resources of both Linux and OpenVMS systems by providing practical hints, tricks, and step-by-step processes for installing and interoperating both systems. If you've heard one of John Wisniewski's many presentations on the subject, you'll find that he also brings his expertise and his own brand of humor to the task of explaining these operating systems to new and experienced programmers and administrators. Covers the capabilities, features, and advantages of both Linux and OpenVMS Offers tested solutions to practical interoperability problems Provides a basis for you to choose the right operating system for your needs.